Enhanced confinement in diverted negative-triangularity L-mode plasmas in TCV. (13th December 2021) - Coda, S; Merle, A; Sauter, O; Porte, L; Bagnato, F; Boedo, J; Bolzonella, T; Février, O; Labit, B; Marinoni, A; Pau, A; Pigatto, L; et al.
Abstract: The favorable confinement properties of negative-triangularity (NT) tokamak configurations were discovered in the TCV tokamak in the late 1990s and were documented over the two following decades, through investigations of predominantly electron-heated plasmas in limited topologies. The most recent experimental campaign in TCV has marked a leap forward, characterized by the development of a variety of diverted NT shapes that are robustly stable with basic Ohmic heating. The application of auxiliary heating, directed now at both electrons and ions (using electron-cyclotron resonance heating as well as neutral-beam injection), has enabled the achievement of record performances for L-mode plasmas, with normalized β values reaching 2.8 transiently (as well as 2 in steady state, but reverting to a limited configuration) and with comparable ion and electron temperatures. The systematic confinement enhancement with NT is confirmed in these experiments. The L-mode existence space is broader than at positive triangularity, with only sporadic transitions to H-mode observed up to 1.4 MW heating power regardless of the magnetic-field-gradient direction relative to the X-point. These experiments are planned to be continued with even higher power following a heating-source upgrade.